The Arian controversy in the Homilies of the Patriarch Photios (Homilies XV and XVI) - Afinogenov Dmitrii (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2014)
In his two homilies dedicated to the Arian controversy (the only surviving of the original ﬁve) Photios uses diﬀerent methods to actualize the matter for the broad Byzantine public, mainly in connection with the patriarch’s main concern during his ﬁ rst tenure: the polemics against Iconoclasm. The Arianism was chosen as a purely logical juxtaposition to the latter, where the real gradual progress of iconoclast tendencies is compared to a theoretical construction of Arianism which has little to do with the actual developments in the IVth century. The comparison of the Iconoclast heresiarch John the Grammarian to Arius is chieﬂy aimed at justifying the permanent deposition of Iconoclast priests even in case of repentance, declared by the Patriarch Nikephoros in 815 and carried out by Methodios in 843. The triadological considerations in the Homily XVI do not in fact pertain to anti- ﬁ lioque polemics, but rather represent a traditional Eastern conception. This, as well as the intense and negative attention to the Council of Sardica suggest the date 861, when Photios had to argue against the applicability of this council’s 10th canon to his promotion to patriarch from a layman.